Neuropathologic Findings in a Child with a Novel Variant of TBCK-Related Encephaloneuronopathy - Chen, Sonja; Zakka, Fouad; Khedr, Salwa; Mangray, Shamlal; Massingham, Lauren; de la Monte, Suzanne M. (Journal of Pediatric Neurology, 2020)
A 3-year-old girl with developmental delays, hypotonia, and generalized seizures was diagnosed with a novel variant of a heterozygous mutation in the TBC1 domain containing kinase (TBCK) gene. Postmortem findings revealed severe hypotrophy of cerebral white matter, hypogenesis of the corpus callosum with reduced myelination and oligodendrocyte populations, and reactive gliosis, and venous angiomas of the cerebrum, brainstem, and cerebellum white matter. This report is the first to link a TBCK gene mutation to impaired white matter development with the targeting of central nervous system myelin and oligodendrocytes. The mechanism may involve inhibition of signaling through (mTORC1).
Keywords: TBCK; brain pathology; cerebral white matter